Village Complaints Application System Based On Android Webview - Ginanjar Agung Sudrajat; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2022)
Many residents in the village of Entalsewu, Buduran District, Sidoarjo Regency, often complain about the situation in the village. Complainants do not know where to go to convey their complaints in the village environment. For example, roads that are damaged and have potholes due to frequent vehicles and extreme rainy weather along the roads in Entalsewu village and also the dead and dim public street lighting (PJU) have not been repaired so that road users experience accidents at night, many residents' houses flooded water that enters the house. Therefore, to overcome this problem, the author designed a village complaint application system based on android webview with a case study of village development. Which aims to make it easier for the public to make complaints in the village of Entalsewu, Buduran District, Sidoarjo Regency. This android application can be used by the public to make complaints online. This application can also make it easier for the village government to respond to community complaints. In this study, the author uses the Waterfall method as a process or flow of research results.